MODERN MEDIA WORLD: KEY CONCEPTS AND ANALYSIS OF INFORMATION SOURCES - Ziyatov Abduhoshim Abduvali o’g’li (Journals Park Publishing, 2022)
The development of the state and society in the Republic of Uzbekistan, the growing freedom of speech is making positive changes in the activities of mass media, including internet journalism. In turn, the activities of independent journalists and bloggers are expanding in our country. The article contains information about modern sources of information and blogging
Keywords: Internet journalism. Blog. Blogger. Vlog. Vloggers